Penerapan Pemikiran Ahmad Dahlan Al-Ma'un Revitalisasi Pendidikan Karakter Kebangsaan Fikih Sosial di SMA Labbaik Lahat - Era Afriza; Hafizh Maulana Nugraha; Muhammad Fauzi; Abu Mansur (LPPM Institut Pendidikan Nusantara Global, 2026)
This study investigates the implementation of Ahmad Dahlan’s interpretation of Al-Ma'un as a foundation for revitalizing national character education through Islamic Religious Education (PAI) with an emphasis on social jurisprudence (fiqh sosial) at SMA Labbaik Lahat. The research is motivated by the urgent need to strengthen students’ national character in the face of globalization, growing individualism, and declining social concern among young people. Contextually read by Ahmad Dahlan, Surah Al-Ma'un underscores the necessity of translating Islamic teachings into tangible social actions, including care for the marginalized (dhuafa), social justice, and humanitarian responsibility, which strongly align with the aims of national character education and the high-school social fiqh curriculum. Employing a qualitative case study design, the study collected data through classroom observations, in-depth interviews with PAI teachers and students, and document analysis of learning materials and school programs. Data were analyzed using thematic procedures consisting of data reduction, data display, and conclusion drawing. The findings demonstrate that integrating Al-Ma'un-based thought into social fiqh instruction strengthens students’ national character values, such as religiosity, social empathy, mutual cooperation, responsibility, and concern for the social environment. Learning activities move beyond a merely normative understanding of fiqh by promoting value internalization through social practice, including acts of care, sharing initiatives, and the habituation of prosocial attitudes in the school context. The study concludes that Ahmad Dahlan’s conception of Al-Ma'un is both relevant and effective as a pedagogical foundation for revitalizing national character education within PAI learning grounded in social jurisprudence at the senior secondary level.